1997
DOI: 10.1515/znc-1997-7-812
|View full text |Cite
|
Sign up to set email alerts
|

Schizokinen, the Siderophore of the Plant Deleterious Bacterium Ralstonia (Pseudomonas) solanacearum ATCC 11696

Abstract: Ralstonia (formerly Burkholderia or Pseudomonas) solanacearum ATCC 11696 - a plant deleterious bacterium - was shown to produce under iron limited conditions of growth an iron complexing compound which facilitated iron uptake into iron-starved cells. The structure of the siderophore was elucidated as 4-[[(3-acetylhydroxyamino)-propyl]amino]-2-[2-[[3-(acetylhydroxyamino)-propyl]amino]-2-oxoethyl]-2-hydroxy-4-oxo-butanoic acid, a compound known under the trivial name of schizokinen. Its partially cyclized form, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The putative cysK-ssd operon does not appear to code for enzymes necessary to synthesize a dihydroxamate siderophore like schizokinen, which R. solanacearum ATCC 11696 reportedly produces (5). A search for homologs of the cysK-ssd operon in various databases revealed a very similar region in the genome of R. metallidurans CH34 that is involved in siderophore production (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The putative cysK-ssd operon does not appear to code for enzymes necessary to synthesize a dihydroxamate siderophore like schizokinen, which R. solanacearum ATCC 11696 reportedly produces (5). A search for homologs of the cysK-ssd operon in various databases revealed a very similar region in the genome of R. metallidurans CH34 that is involved in siderophore production (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We were intrigued by the juxtaposition of these two global-acting transcriptional regulators and wondered whether iron scavenging is required for virulence of R. solanacearum, like it is for several other plant pathogenic bacteria (16). Budzikiewicz et al (5) reported that, like B. megaterium, the R. solanacearum type strain (ATCC 11696; also known as K60) produces the dihydroxamate citrate-containing siderophore schizokinen. Nothing was known about the genetics of schizokinen production in either bacterium, so we used transposon mutagenesis to create R. solanacearum mutants defective in iron-scavenging ability.…”
mentioning
confidence: 99%
“…It was named after its cell division promoting effect observed with Bacillus cultures (200). Its structure was elucidated by degradation and spectral data and confirmed by synthesis (43,202,237,248). For a compilation of details on structural data the review (39) should be consulted.…”
Section: Siderophores With Two Hydroxamic Acid Unitsmentioning
confidence: 99%
“…For a compilation of details on structural data the review (39) should be consulted. Both natural and synthetic schizokinen is accompanied by the cyclized schizokinen A (43,202,237,248). Schizokinen forms a 1:1 complex with Fe 3+ , but at the central hydroxy group acetylated schizokinen yields (Fe 3+ ) 2 Lig 3 .…”
Section: Siderophores With Two Hydroxamic Acid Unitsmentioning
confidence: 99%
“…This molecule is produced by some bacteria (Budzikiewicz et al 1997) and by members of the freshwater cyanobacterial genus Anabaena (Simpson and Neilands 1976;Nicolaisen et al 2008). The presence of schizokinen inhibits the growth of ironlimited cells of the green alga Chlamydomonas reinhardtii (Matz et al 2004).…”
Section: Introductionmentioning
confidence: 99%